2013
DOI: 10.1002/aic.13998
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of dimethyl oxalate to ethylene glycol over mesoporous CuMCM‐41 catalysts

Abstract: The synthesis and utilization of mesoporous Cu‐MCM‐41 catalysts for hydrogenation of dimethyl oxalate to ethylene glycol is described in this article. Physicochemical properties of these Cu‐MCM‐41 catalysts have been investigated by N2‐physisorption, X‐ray diffraction, inductively coupled plasma, N2O titration, transmission electron microscopy, temperature programmed reduction, Fourier transform infrared spectroscopy, and X‐ray photoelectron spectroscopy. It was found that the copper loading significantly infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 41 publications
6
53
0
1
Order By: Relevance
“…The DMO hydrogenation reaction to EtOH comprises several continuous reactions (Table 1), including DMO hydrogenation to MG, MG hydrogenation to ethylene glycol (EG) and deep hydrogenation of EG to EtOH 33,34 . Confinement of reactants and reaction intermediates within such nanochannels could prolong the contact time of these species with the active sites inside the CuPSNTs 35 , which favours the deep hydrogenation reaction and leads to a higher selectivity to EG or ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The DMO hydrogenation reaction to EtOH comprises several continuous reactions (Table 1), including DMO hydrogenation to MG, MG hydrogenation to ethylene glycol (EG) and deep hydrogenation of EG to EtOH 33,34 . Confinement of reactants and reaction intermediates within such nanochannels could prolong the contact time of these species with the active sites inside the CuPSNTs 35 , which favours the deep hydrogenation reaction and leads to a higher selectivity to EG or ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation of MN on metal surfaces has also been investigated by several groups [7][8][9][10]12]. Peck and co-workers performed A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 4 auger electron spectroscopy (AES), low-energy electron diffraction (LEED), and temperature-programmed desorption (TPD) studies on MN dissociation on Pt(111) and Pt-Sn alloys [9,10]. They found that the activation of MN is very facile to produce adsorbed CH 3 [7,8].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, due to the shrink of oil resources and the continuous increase of EG demand, an alternative EG synthesis technology called coal to ethylene glycol (CTEG) has attracted substantial attention [1,[4][5][6]. CO catalytic coupling with methyl nitrite (MN) to dimethyl oxalate (DMO) is the crucial step in the conversion of inorganic C1 to organic C2 in CTEG, and thus it is considered to be one of the most important applications in C1 chemistry [5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high reaction activity and low cost, Cu-based catalyst has been widely used in DMO hydrogenation to EG. [33][34][35][36] …”
Section: Catalysts For Dmo Hydrogenation To Eg Reactionmentioning
confidence: 99%
“…The other supports can be divided into two categories: simple oxides (TiO 2 , [52] ZnO, [53] Al 2 O 3 , [54] ZrO 2 [55] etc.) and molecular sieves (SBA-15, [56] ZSM-5, [57] MCM-41, [58] HMS, [59] etc.). The effect of TiO 2 crystal phase and the interaction between Cu and TiO 2 were systematically investigated by Dai group.…”
Section: Support Effectmentioning
confidence: 99%